Pengembangan Media Pembelajaran Teks Multimodal untuk Meningkatkan Keterampilan Membaca Pemahaman Teks Berita Siswa Kelas VII - Ni Made Lidia Hindriyani; I Nyoman Sudiana; Ni Made Rai Wisudariani (EduInovasi: Journal of Basic Educational Studies, 2025)
This study is to enhance the reading comprehension abilities of class VII students at SMP Negeri 2 Kuta by describing the prototype and evaluating the degree of usefulness of multimodal text learning materials. Research and development (R&D) is the research methodology employed. Twenty-five seventh-grade students from SMP Negeri 2 Kuta made up the study's population. The study's findings show that there are three different ways to present multimodal text learning materials for news text reading comprehension skills: (1) narrative text presentations, (2) infographic presentations, and (3) informative video presentations. One flip book platform combines the three learning resources. Additionally, the results of the teacher and student questionnaires on the practicality criteria showed that teacher 1 had an average score of 4.8 on the very practical criterion, while teacher 2 had an average score of 5.0 on the very practical criterion. Students 1 and 5 also scored 5.0 on the very practical criterion, while students 2, 3, and 4 scored 4.8 on the very practical criterion.